Service experience of the department of gynecology at La Plata, in the extended class III classification Pap - Lagrutta, J. (2015)
There are various causes that can originate an extended class III: carcinoma, epithelial hyperplasia, trichomoniasis, nonspecific colpitis, pregnancy, vaginal atrophy, ectrapionitis. In the presence of an extended III it is necessary to make a careful examination of the neck (colposcopy examination flow, etc.) and perform directed biopsy in the presence of any suspicious image. Being the most frequent cause widespread trichomoniasis, yet we must not discard their possible association with carcinoma (two cases in our statistics) and make a colposcopic examination of the neck and repeat cytology once cured the condition.